2020
DOI: 10.1007/s10967-020-07326-y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption properties of iodine on fused silica surfaces when evaporated from tellurium in various atmospheres

Abstract: The evaporation of iodine containing species from tellurium has been investigated together with their adsorption behavior on a fused silica surface. In inert gas, the formation of two species was observed with adsorption enthalpies of around − 90 to − 100 and − 110 to − 120 kJ/mol, respectively. For reducing environments, a single species identified as monatomic iodine was observed with an adsorption enthalpy around − 95 kJ/mol. In oxidizing conditions, species with low adsorption enthalpies ranging from − 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Because the tellurium concentration in LBE is rather high and iodine is formed from tellurium distributed in the LBE matrix when irradiating the LBE samples, potential formation of tellurium iodides must be considered when interpreting the results. Indeed, depositions with adsorption enthalpies between − 110 and − 120 kJ mol −1 observed in a recent thermochromatography study on neutron irradiated pure tellurium samples were attributed to tellurium iodides [19]. Thermodynamic data on tellurium iodides are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Because the tellurium concentration in LBE is rather high and iodine is formed from tellurium distributed in the LBE matrix when irradiating the LBE samples, potential formation of tellurium iodides must be considered when interpreting the results. Indeed, depositions with adsorption enthalpies between − 110 and − 120 kJ mol −1 observed in a recent thermochromatography study on neutron irradiated pure tellurium samples were attributed to tellurium iodides [19]. Thermodynamic data on tellurium iodides are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…[44,53] Experiments with caesium-doped LBE indicate that the caesium released from LBE is not adsorbed to steel and fused silica surfaces in thermochromatography experiments but rather reacts with these surfaces at temperatures between 400 and 700 °C, leading to a fixation of the volatile species. [44,54] Similar studies performed for polonium revealed that polonium, when it is evaporated in elemental form from samples that do not contain elements of the LBE matrix, adsorbs to steel slightly more strongly than to fused silica surfaces. More importantly, the formation of volatile species observed in similar experiments in fused silica columns with moist inert and reducing carrier gases was not observed in steel columns, indicating that the steel used as construction material for MYRRHA can suppress the formation of these species.…”
Section: Recent Results: the Euratom H2020 Project Myrtementioning
confidence: 81%
“…Thermochromatography studies on iodine evaporated from LBE indicate that in helium and hydrogen gas bismuth monoiodide is formed and deposited at relatively low temperatures (100-180 °C). [44,52] In oxidising atmosphere, even more volatile species such as monatomic iodine and iodine oxides are formed. However, the adsorption of iodine evaporated from LBE Fig.…”
Section: Recent Results: the Euratom H2020 Project Myrtementioning
confidence: 99%